Folie à deux? How Mavericks shape the relationship between the dark triad and negative deviant behaviours through malevolent creativity - Silva, D.; Junça-Silva, A.; Pinheiro, P. (Personality and Individual Differences, 2025)
This study used the trait activation theory to develop a conceptual model that explained how and when the dark triad state influenced negative deviant behaviours (NDB). For that, we tested malevolent creativity as a mediating variable and maverickism as a moderator. Diary data was collected from 54 working adults (324 measurement occasions). The multilevel results showed that (1) all the DT states had a positive relationship with NDB through malevolent creativity, and (2) maverickism moderated the indirect effect of machiavellianism and narcissism, but not for psychopathy. Specifically, the relationship between machiavellianism and narcissism and NDB via malevolent creativity became stronger for those who scored lower on maverickism. Practical and theoretical implications are discussed.